Prevalencia de estrategias de enseñanza del inglés en docentes de tres instituciones educativas públicas nivel secundaria, Iquitos 2022 - Freitas Garcia, Lupe Elena (2023)
This study aimed to characterize the diversity of approaches used for teaching English among teachers of three public secondary schools in Iquitos in 2022. For this purpose, the research design was the application in the field, transversal in obtaining data and univariate, through the descriptive type of research. To collect information and obtain data from teachers, the survey method and a questionnaire validated by experts were used. This instrument was applied to 22 teachers who teach English in the three educational institutions that represented both the population and the sample of the study. The prevalent teaching strategies in three public secondary educational institutions in Iquitos are active acquisition of knowledge (77.3%), student motivation (68.2%), and metacognition and self-regulation (63.6%). These results highlight an educational approach focused on participation and the development of critical skills and self-regulation.